2011
DOI: 10.3382/ps.2010-00956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and inorganic forms of selenium in diets on turkey semen quality

Abstract: The effects of Se supplementation and its organic or inorganic form on semen quantitative parameters (ejaculate volume, sperm concentration, and total number of sperm) and biochemical parameters of seminal plasma (protein concentration, acid phosphatase activity, superoxide dismutase activity, and total antioxidant capacity) were investigated over a 25-wk reproductive season. Additionally, DNA fragmentation and motility characteristics of turkey spermatozoa were measured. The parameters of turkey semen in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…Therefore a higher resistance to oxidative stress should be expected when selenium is provided. A positive effect of selenium on sperm concentration and morphology has been also reported by other authors in men (26,32) and various animal species (18,23,24,33,34,37). On the contrary, some studies have reported that there were no positive effects of selenium supplementation on sperm quality either in humans (12,15) or boars (13).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore a higher resistance to oxidative stress should be expected when selenium is provided. A positive effect of selenium on sperm concentration and morphology has been also reported by other authors in men (26,32) and various animal species (18,23,24,33,34,37). On the contrary, some studies have reported that there were no positive effects of selenium supplementation on sperm quality either in humans (12,15) or boars (13).…”
Section: Discussionsupporting
confidence: 72%
“…GPx is present in canine spermatozoa and seminal plasma and plays the main role in the decomposition of hydrogen peroxide (19,35). Studies on humans (26,32), boars (18,23,24,34), bulls (37), mice (39), and turkeys (33) demonstrated an evident connection between deficiency in selenium and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…In another experiment (Słowińska et al 2011), dietary Se supplementation did not affect the antioxidant properties of turkey seminal plasma, however it increased the volume and concentration of sperm.…”
Section: Discussionmentioning
confidence: 90%
“…Many previous studies attributed the high biological effect of SY to l-selenomethionine (l-Se-Met), a Se analog of l-methionine (l-Met), which was the most abundant Se chemical form in SY (Kelly and Power 1995;Cobanova et al 2011;Slowinska et al 2011). Besides, l-Se-Met is also the main Se species in cereals, forage crops, soybeans, and grassland legumes (Whanger 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, l-Se-Met is also the main Se species in cereals, forage crops, soybeans, and grassland legumes (Whanger 2002). Numerous studies have since established that l-Se-Met and SY are suitable for nutritional Se supplementation (Schrauzer 1998;Li et al 2011;Slowinska et al 2011;Wang 2011b).…”
Section: Introductionmentioning
confidence: 99%